2022
DOI: 10.3390/pharmaceutics14102208
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles: A Potential Therapy for Diabetes Mellitus and Diabetic Complications

Abstract: As a novel cell-free strategy, mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) inherit the therapeutic potential of donor cells, and are widely used for the treatment of many diseases. Increasing studies have shown that MSC-EVs transfer various bioactive molecules to create a beneficial microenvironment, thus exerting protective roles in diabetic mellitus (DM) and diabetic complications. To overcome the limitations of natural MSC-EVs such as heterogeneity and insufficient function, several modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 172 publications
0
7
0
Order By: Relevance
“…For example, in the model of type I diabetes and retinitis, MSC EVs are as effective as MSCs in inhibiting autoimmunity. In addition, the effect of MSC-EVs on acute kidney injury is similar to that of MSCs [9]. These observations indicate that MSC EVs can serve as substitutes for MSC based cell therapy.…”
Section: Mesenchymal Stem Cells-derived Evsmentioning
confidence: 53%
“…For example, in the model of type I diabetes and retinitis, MSC EVs are as effective as MSCs in inhibiting autoimmunity. In addition, the effect of MSC-EVs on acute kidney injury is similar to that of MSCs [9]. These observations indicate that MSC EVs can serve as substitutes for MSC based cell therapy.…”
Section: Mesenchymal Stem Cells-derived Evsmentioning
confidence: 53%
“…Clinical studies have confirmed the ability of MSCs to evolve into insulin-producing cells and secrete healing factors, positioning them as key players in T1D treatment ( 26 ). Furthermore, engineered MSC-derived EVs are being developed to enhance regenerative efficacy, overcoming natural limitations ( 27 ). Proteomic analyses of MSC exosomes from various sources have revealed that shared mechanisms, notably extracellular matrix interactions, are crucial for their regenerative impact ( 28 ).…”
Section: Background On Mscsmentioning
confidence: 99%
“…Compared to existing treatments like laser photocoagulation, VEGF inhibitors, and corticosteroids, which often target specific symptoms or disease aspects, MSC-EVs could potentially offer a more comprehensive approach by addressing inflammation, oxidative stress, and cell death. However, for MSC-EV therapy to be clinically feasible, improvements in the formulation and administration techniques are necessary to enhance delivery, efficacy, and the practicality of their use in clinical settings ( Sun et al, 2022b ).…”
Section: Nrf2/ho-1 Regulation In Human Diseasesmentioning
confidence: 99%